Multivariate Analysis on The Determinants of Work Fatigue Factors for Nurses Inpatient Care at RSUD Arifin Achmad Hospital Pekanbaru - Devi Purnama Sari; Tjipto Suwandi; Endang Purnawati Rahayu (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
This research aims to analyze the relationship of age, sex, years of work, nutritional status and work shifts to work fatigue. This research is a quantitative observational analytic study with an analytic cross-sectional study design and a sample size of 60 people. Primary data were collected by direct observation, interviews with the KAUPK2 questionnaire and measurement of Lassidaya L77. The results of bivariate analysis showed a relationship between age and nurse work fatigue (p = 0.026). There was no gender relationship (p = 0.552), years of service (p = 0.104), nutritional status (p = 0.288) and work shift (p = 0.132) with work fatigue. Arifin Achmad Hospital (p = 0.009) POR 12,199 (95%: 1,847 - 80,575). Counfonding work shifts with tenure. There is no relationship between sex and nutritional status with the incidence of work fatigue. Nutritional status (p = 0.571), POR 1.458 (95%: 0.395 - 5.379). Nutritional status (p = 0.866) 1.062 POR (95%: 0.527 - 2.140). The age variable was not included in the multivariate analysis because it was homogeneous. From the results of the analysis it was concluded that the working period ≥ 10 years affects work fatigue compared to ten years <10 years.